In This Issue. (Computer (00189162), 2021)
Computer receives a fair number of submissions relating to software development, software engineering, composing systems from components, testing and validation, and requirements elicitation. Because these topics remain a technical mainstay of the IEEE Computer Society, we even launched a new software engineering column in Computer this year.